Determination of spatial proximity between the N-terminus and cocaine binding site of the dopamine transporter by FRET - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Objective: The dopamine transporter (DAT) mediates uptake of dopamine from the synaptic cleft and provides rapid termination of neurotransmission. It is the site of action for different drugs of abuse, including cocaine and amphetamine. Serine 7 and 12 at the N-terminus were found to be critical residues in phosphorylation. Here, we addressed spatial proximity site relationship of N-terminal extension with respect to cocaine binding in wild type and Ser7/12Asp and Ser7/12Ala mutants. Materials and Methods: The yellow-fluorescent protein (YFP) and mutations were introduced into the N-terminus of the hSynDAT by a two-step PCR. Dopamine uptake assays were performed and Forster resonance energy transfer (FRET) distances were determined using donor bleach method in a confocal microscope. Results: All N-terminally YFP-tagged DAT constructs were properly trafficked to the cell surface. K-m values were 0.76, 0.75 and 1.24 mu M for wild-type, Ser7/12Ala and Ser7/12/Asp constructs, respectively. FRET efficiency value was found to be 0.15 for YFP-labeled DAT while corresponding estimated distance was calculated as 68.4 angstrom. FRET efficiencies of other constructs were negative and no energy transfer was detected. Conclusion: Our data show that extreme end of N-terminus is in FRET distance from cocaine binding site and mutation of critical serine residues to the phosphorylation-mimicking form (Ser7/12Asp) have increased this distance.
Keywords: Dopamine transporter (DAT); Cocaine binding; Forster resonance energy transfer (FRET); N-terminus of DAT; Phosphorylation of DAT